Communicating epidemiological results through alternative indicators: Cognitive interviewing to assess a questionnaire on risk perception in a high environmental risk area - Farinella, Domenica (Cogent social sciences, 2017)
Participatory approaches to environmental research and decision-making require that all social stakeholders are involved from the onset of the debate. In such a setting, communication among different expertise is crucial, but language and technicalities may represent a barrier. In the clinical setting, decisions regarding treatment preferences may be influenced by the summary statistics used, but, according to the literature, no study has compared different statistical indicators for risk communication in environmental epidemiology. In this paper, we report on the qualitative results of the cognitive interviews conducted for assessing two questionnaires devoted to investigating risk perception when selected epidemiological results are communicated, by using different statistical indicators of health impact and uncertainty. The initial questionnaires were tested on 15 people residing in the high environmental risk area of Livorno (Italy). Cognitive interviewing led to substantial revision of the initial drafts. Moreover, it highlighted the difficulty of communicating statistical uncertainty and the need to account for the complex interaction between mathematical skills, affective factors and individual a priori knowledge on environmental risk perception.